Pengembangan Keterampilan 4C (Critical, Thinking, Creativity, Communication , and Collaboration) dalam Pembelajaran IPS untuk Menjawab Tantangan Abad 21 - Jihan Nurhamidah; Arladia Hafsya; Oman Farhurohman (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The 21st century presents significant challenges in education, including the need for critical thinking, creativity, communication and collaboration (4C) skills. This article explores the importance of 4C skills development in Social Science learning to prepare students for the era of globalization and the industrial revolution 4.0. Through a systematic literature review of national and international scientific articles, this research identifies the relevance of 4C skills in improving analytical ability, team collaboration, innovation, and interpersonal communication. The results show that the integration of 4C skills in social studies learning can foster social intelligence, empathy and multicultural awareness. With a holistic approach, social studies education can be an effective tool in preparing students to compete globally amid the complexity of the modern world.